2013
DOI: 10.1136/heartjnl-2013-304158
|View full text |Cite
|
Sign up to set email alerts
|

Value of D-dimer and C reactive protein in predicting inhospital death in acute aortic dissection

Abstract: D-dimer ≥5.67 μg/mL, CRP ≥11.21 mg/L and type A acute AD were important risk factors and independently associated with acute AD inhospital death.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
122
1
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 123 publications
(129 citation statements)
references
References 31 publications
4
122
1
2
Order By: Relevance
“…D‐dimer has recently gained attention as an outcome predictor for patients with AAD 13, 21, 22, 23. Wen et al (cutoff, 5.67 μg/mL)22 and Gorla et al (cutoff, 9.0 μg/mL)23 reported that a D‐dimer concentration above the cutoff level was a risk factor for in‐hospital mortality in patients with ATAAD or acute type B aortic dissection.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…D‐dimer has recently gained attention as an outcome predictor for patients with AAD 13, 21, 22, 23. Wen et al (cutoff, 5.67 μg/mL)22 and Gorla et al (cutoff, 9.0 μg/mL)23 reported that a D‐dimer concentration above the cutoff level was a risk factor for in‐hospital mortality in patients with ATAAD or acute type B aortic dissection.…”
Section: Discussionmentioning
confidence: 99%
“…Wen et al (cutoff, 5.67 μg/mL)22 and Gorla et al (cutoff, 9.0 μg/mL)23 reported that a D‐dimer concentration above the cutoff level was a risk factor for in‐hospital mortality in patients with ATAAD or acute type B aortic dissection. Huang et al (cutoff, 6.1 μg/mL) also reported that a D‐dimer concentration above the cutoff level was a risk factor for both in‐hospital and long‐term mortality among patients with ATAAD, including some who underwent conservative therapy 21.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Ayrıca son on yıldaki çalışmalar, inflamasyonun AD'nin hem patogenezinde etkili olduğunu, hem de olumsuz sonuçların gelişmesinde rol oynadığını göstermiş-tir (7)(8)(9) . C-reaktif protein (CRP), fibrinojen ve D-dimer gibi bazı inflamatuvar belirteçlerin AD'li hastalarda prognoz ile ilişkili olduğu saptanmıştır (10,11) . Bunlara ek olarak, trombosit sayı-sı ve fibrin yıkım ürünleri gibi trombotik belirteçlerinde akut AD'li hastalarda hastane içi mortalitede bağımsız belirleyiciler olduğu gösterilmiştir (10,(12)(13)(14) .…”
Section: Introductionunclassified
“…C-reaktif protein (CRP), fibrinojen ve D-dimer gibi bazı inflamatuvar belirteçlerin AD'li hastalarda prognoz ile ilişkili olduğu saptanmıştır (10,11) . Bunlara ek olarak, trombosit sayı-sı ve fibrin yıkım ürünleri gibi trombotik belirteçlerinde akut AD'li hastalarda hastane içi mortalitede bağımsız belirleyiciler olduğu gösterilmiştir (10,(12)(13)(14) . Trombosit-lenfosit oranı (TLO) son zamanlarda farklı kardiyak hastalık durumlarında, çeşitli kardiyovasküler olaylar ile ilişkilendirilmiş bir belirteçtir (15)(16)(17) .…”
Section: Introductionunclassified